AgNO3 dependent modulation of glucose mediated respiration kinetics in Escherichia coli at different pH and temperature / Radin Nur Afiqah Radin Abd Halim - Radin Abd Halim, Radin Nur Afiqah (2019)
Silver nitrate (AgNO3) has been widely used as an antimicrobial agent. However, there is a lack of information on its microbial anti-physiologic role. Although it is known that AgNO3 interferes with the microbial respiration, its action at various glucose concentration, pH and temperature has not been elucidated. Therefore, this study aimed to investigate the time dependent modulation of glucose mediated respiration of E. coli at different pH, temperature and various concentration of silver nitrate; concentration dependent impact of glucose upon the respiration of E. coli; and preferential binding of AgNO3 upon the respiratory enzymes by computational methods. Clark type electrode was used to measure E. coli oxygen consumption. The physical state of the microbe was assessed using environmental scanning electron microscope.